2019
DOI: 10.18488/journal.136.2019.41.1.13
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Deceptive Marketing Communication on the Brand Equity of Private Higher Education Institutions (PHEIs) in the Northwest and Southwest Regions of Cameroon

Abstract: The problem of falling educational standards in Cameroon has been posed severally from a purely educationist perspective. This study however goes from the premise that the liberalization of the Higher Educational Sector in the early 90s ushered in questionable capitalistic business practices by promoters of PHEIs in a bid to uphold their economic bottom lines as they would in any classical sector. This paper examines an extreme unethical mercantilist practice of deceptive marketing communication and its conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…However, in an attempt to increase brand awareness, higher education institutions should avoid any deceptive communications. This is because research (Joyvice et al, 2019) shows that while marketing communication deception may seem like a rewarding strategy in the short run (favorable enrollment decisions to attract enrollees), it erodes the brand equity of these institutions in the long run. Similarly, a study by Pringle and Fritz (2019) revealed that the content shared on social media channels, while appears trustworthy, was sometimes used against the university when they are perceived to be dishonest or threatened institutional norms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in an attempt to increase brand awareness, higher education institutions should avoid any deceptive communications. This is because research (Joyvice et al, 2019) shows that while marketing communication deception may seem like a rewarding strategy in the short run (favorable enrollment decisions to attract enrollees), it erodes the brand equity of these institutions in the long run. Similarly, a study by Pringle and Fritz (2019) revealed that the content shared on social media channels, while appears trustworthy, was sometimes used against the university when they are perceived to be dishonest or threatened institutional norms.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Joyvice et al (2019) examines an extreme unethical mercantilist practice of deceptive marketing communication and its consequences on the brand equity of private higher education (PHEIs) in the Northwest and Southwest Regions of Cameroon. Based on their findings, they concluded that the majority of private higher education institutions actually engage in marketing communication deception in an effort to attract enrollees, and this actually pays off in the short run as most enrollees make enrollment decisions believing the claims propagated by their prospective PHEIs.…”
Section: Branding In Higher Educationmentioning
confidence: 99%
“…In this regard, Pharr (2019) encourages colleges and universities to develop valuable and engaging authentic brand content. However, Joyvice et al (2019) suggest avoiding deceptive marketing communications. The direct positive significant relationship between perceived quality and brand trust indicates the importance of perceived quality in building brand trust.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Brand awareness is an important factor for creating a strong university brand and brand equity as it directly and/or indirectly influences the other brand equity dimensions, which is consistent with the brand equity conceptualization (Aaker, 1991, 1996, Keller, 1993, 2013. While higher education institutions could utilize social media to increase awareness and build university brand (i.e., Belanger et al, 2014;Pringle and Fritz, 2019), they should avoid any deceptive communications, as it erodes the brand equity of these institutions in the long run (Joyvice et al, 2019).…”
Section: Discussionmentioning
confidence: 99%